Pengaruh Premi, Pengetahuan Dan Religiusitas Terhadap Keputusan Nasabah Berasuransi Di PT. Asuransi Jiwa Syariah Al-Amin Jambi - Sari, Septia Arnisa (ITB AAS INDONESIA Surakarta, 2024)
This study aims to see the effect of premiums, knowledge and religiosity on insurance customer decisions at PT. Al-Al-Amin Jambi Sharia Life Insurance. This study has independent variables (variables that influence) and dependent variables (variables that are influenced). This type of research is quantitative research. Data collection obtained is by means of a questionnaire (questionnaire). The sample in this study amounted to 61 people. The analysis used is multiple regression analysis. After partial testing, it was concluded that the premium variable had a significant effect on the insurance customer's decision. In addition to the premium factor, there is also a significant influence of knowledge variables on insurance customer decisions. Finally, the religiosity variable has a significant effect on insurance customer decisions. Based on the results of the F test (simultaneous) it can be concluded that the variable premium, knowledge and religiosity together have a significant influence on the decision of insurance customers at PT. Al-Amin Sharia Life Insurance.